ALTERNATIVE VAT POLICIES FOR SUSTAINABLE MENSTRUAL PRODUCTS IN INDONESIA - Suci, Saraswati Nirmala; Muamarah, Hanik Susilawati (Jurnal Akuntansi dan Keuangan Indonesia, 2025)
Background: Sustainable menstrual products currently face the same VAT rate as conventional products, making them less affordable and slowing their adoption. This price gap drives consumers toward cheaper disposable alternatives, increasing non-recyclable waste and environmental risks. Addressing this imbalance is essential to advancing sustainability and menstrual equity. Method: This study conducted in-depth interviews with officials from the Directorate General of Taxes, the Fiscal Policy Agency, the Ministry of Environment and Forestry, academicians, and a sustainable product manufacturer. Data were analyzed using the Regulatory Impact Assessment (RIA) framework to evaluate four VAT policy alternatives: normal VAT, VAT exemption, non-collected VAT, and VAT on a certain amount. Findings: The non-collected VAT option provides the greatest overall benefit for both the public and industry. It enhances affordability, encourages the adoption of sustainable menstrual products, and reduces environmental burdens. Conclusion: A non-collected VAT policy is crucial for expanding access, supporting environmental objectives, and strengthening gender-responsive fiscal policy. Effective implementation requires coordinated planning and continuous monitoring. Novelty/Originality: This study is among the first to assess VAT options for sustainable menstrual products using an RIA approach, integrating fiscal reform, environmental sustainability, and gender-sensitive budgeting.